The impact of Jigsaw strategy on cooperative learning on Arabic language skills among Education College students at Kuwait University. - الوتار نوري (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This study aimed to identify the effectiveness of the Jigsaw strategy for cooperative learning in developing Arabic language skills among students of the College of Education at Kuwait University. To achieve the objectives of the study, the descriptive analytical method and the experimental method were used based on the design of the two groups (experimental and control), while the study tool was used to collect data. It was an achievement test, which was applied to the study sample consisting of (138) female students from the College of Education at Kuwait University, (70) within the control group, and (68) within the experimental group. As for the study variables, they were a strategy. Jigsaw (the independent variable), and Arabic language skills (the dependent variable). The study concluded a set of results, the most important of which is the presence of a statistically significant difference at the significance level (α ≤ 0.05) between the average scores of the female students in the experimental and control groups in the post-application of the achievement test in language skills. Arabic, for the benefit of the experimental group in which the Jigsaw strategy was used. The results also showed that the effect of this strategy was significant in improving the Arabic language skills of female students. The study recommended a number of recommendations, the most important of which is the necessity of informing teachers of the importance and benefits of the Jigsaw strategy on teaching the Arabic language to students. Encouraging them to use it, and the necessity of informing students of the importance of this strategy and its ability to enhance their academic achievement, which increases their acceptance of it and their better integration into its application, and developing a guide for teachers that helps them apply this strategy in order to achieve the best possible results.